Gluten-sensitive enteropathy: Synthesis of antigliadin antibody in vitro. Issue 12 (December 1974) - Falchuk, Z. Myron; Strober, Warren
Abstract : The intestinal mucosa of patients with gluten-sensitive enteropathy responds to gluten challenge in vivo with a striking increase in IgA and IgM synthesis. Whether this increase in immunoglobulin synthesis is due in some part to the production of antigliadin antibodies is examined. Using an affinity chromatography technique it has been demonstrated that in six of seven patients with gluten-sensitive enteropathy approximately half of the net increase in IgA and IgM synthesis occurring after gluten challenge can be attributed to the synthesis of antigliadin antibody. These data strengthen the hypothesis that immunological phenomena are related to the pathogenesis of glutensensitive enteropathy.